2017
DOI: 10.1016/j.pec.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Treatment decision-making in chronic diseases: What are the family members’ roles, needs and attitudes? A systematic review

Abstract: Physicians should include FMs in treatment decision-making when the patients and their FMs wish to be included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 65 publications
4
94
0
2
Order By: Relevance
“…Consistent with previous reviews (Doody et al, ; Lamore, Montalescot, & Untas, ), this review demonstrated that families are often uninvolved in SDM, although they supported treatment decisions. Because most consumers preferred family involvement, it is recommended to provide a range of approaches to engage families in SDM.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Consistent with previous reviews (Doody et al, ; Lamore, Montalescot, & Untas, ), this review demonstrated that families are often uninvolved in SDM, although they supported treatment decisions. Because most consumers preferred family involvement, it is recommended to provide a range of approaches to engage families in SDM.…”
Section: Discussionsupporting
confidence: 87%
“…Notably, family involvement can impact them negatively, and they might feel burdened due to the medical information and long‐term care. This means that MHPs should offer appropriate information and effective psychosocial support to reduce their burden (Lamore et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 30 European countries, among 1546 respondents, 34.2% said they were not involved in treatment decision making, and 17.2% said they felt rushed to make a decision . Of those, 200 were care partners (CPs), 59.0% said they helped the PwP to prepare a list of questions, and 46.5% helped to prepare a list of symptom changes prior to consultations, underscoring the role of CPs, including spouses, family members or informal caregivers, in PCC . With respect to PD, a six‐psychiatrist panel rated information provided during interviews with 223 PwP and separately by their CPs and judged that 71 (31.4%) CPs were critical for determining a psychiatric diagnosis .…”
Section: Introductionmentioning
confidence: 99%
“…The results in this review are presented in a narrative method (as described in Lamore, Montalescot, and Untas [2017]). One of the researchers (OKV) utilized a table to keep a record of findings from each study, and to highlight arising codes for each article.…”
Section: Methodsmentioning
confidence: 99%